Al-Ghazali’s intellectual legacy: balancing philosophy, faith, and human nature - Abdul Razak, Mohd Abbas; Fatah Yasin, Raudlotul Firdaus (Department of Communication, KIRKHS, IIUM, 2024)
Abu Hamid Muhammad ibn Muhammad al-Ghazali, a celebrated figure during the Islamic Golden Age, is more commonly known as Imam Al-Ghazali (450H/1058 – 505H/1111). He was an eminent Muslim jurist, Sufi scholar, and thinker. Recognizing Al-Ghazali’s great potential, the Seljuk regime appointed him as their scholar to counter challenges posed by philosophers, Batiniyyah, rationalists, and others. As a versatile scholar capable of debating and reasoning with opponents, Al-Ghazali earned the title “Hujjatul Islam” (Proof of Islam). Despite being identified as a philosopher by some, Al-Ghazali distanced himself from this label due to the controversies surrounding philosophers of his time, such as Al-Kindi (801-873), Al-Farabi (872-950), and Ibn Sina (980-1037).